Developing a lean benchmarking process to monitor the carbon efficiency in precast concrete factories-a case study in Singapore - Wu, Peng; Pienaar, J.; O'Brien, D. (2013)
The lean production philosophy was developed in the automobile industry and put into practice in the manufacturing industry to reduce waste, inventory and improve productivity. The lean concept has recently been introduced to the manufacturing industry to meet the challenge of sustainable development. However, it seems that the concept of sustainable development was defined too broadly for the manufacturers to guide their preferred decisions and behaviours. This research aims to narrow down the concept of sustainable development and focus on the carbon emissions that can be reduced by applying the lean concept in the precast concrete factories. The results demonstrate that the lean production philosophy can help precasters to reduce the level of carbon emissions, in terms of reducing waste and eliminating unnecessary energy consumption in multi-handling, multi-delivery, maintaining inventory and other non-value adding activities, in line with its concentration on eliminating non-value adding processes. An amount of 5.80% carbon emissions can be reduced in the production process for a specific type of precast concrete column. The lean benchmarking process provided in this study is helpful for the precasters to monitor the carbon efficiency in the precast concrete factories. In addition, the analysis provides good practice guidance when precasters are trying to reduce carbon emissions to meet guidelines from regulatory authorities.